Evaluation of ebony as a potential selectable marker for genetic sexing in Aedes aegypti - Katerina Nikolouli; Austin Compton; Zhijian Jake Tu; Kostas Bourtzis (Parasites & Vectors)
Abstract Background Aedes aegypti is expected to invade previously unoccupied areas, mainly due to the climate change, the increase in travel and trade activities and the continuous transformation of the rural environment into urban areas. The sterile insect technique (SIT), which relies on the mass production and release of sterile males, is an environmentally friendly approach that can be applied for population control of Ae. aegypti. SIT programs can be greatly benefited by a genetic sexing strain (GSS) and a reliable sex sorting system to minimize any accidental female release. Visually detectable or conditionally lethal selectable markers can be used for the development of new GSSs. In this study, we evaluated the suitability and competence of a mutant Ae. aegypti ebony strain for the development of a new GSS. The ebony gene is known to be involved in the pigmentation pathway of several dipteran insects, including Ae. aegypti. Methods An ebony gene knockout was developed though CRISPR/Cas9 mutagenesis. G0 individuals with the desired phenotype were crossed, and progeny were screened in every generation. PCR and sequencing were performed using gDNA from a pulled leg to determine the mutant genotype. Quality control tests, including pupae and adult recovery rates, male sex ratio and fecundity, were applied to the ebony mutant line to determine whether the mutation confers any fitness cost. Results An Ae. aegypti ebony knockout mutant carrying a 5-bp deletion was obtained, which presented darker head and siphon phenotypes at the larval stage. However, genetic analysis revealed that this ebony mutation results in incomplete penetrance and variable expressivity. The establishment of a pure ebony mutant line was not possible because of the fitness costs conferred by the mutation. Conclusions In this study, the adequacy and suitability of the ebony gene as a selectable marker for the development of a GSS in Ae. aegypti were assessed. Despite its clear phenotype early in larval development, the homozygous mutant line presented phenotypic inconsistency and loss of fertility. These drawbacks clearly indicate that this particular mutation is not suitable for the development of a new GSS. Nonetheless, it cannot be excluded that a different mutation will lead to a different expression and penetrance profile and a viable homozygous mutant line. Graphical Abstract